Pengaruh Perilaku Belajar, Kecerdasan Emosional Dan Sistem Pembelajaran Online Terhadap Pemahaman Akuntansi - Elyn Rusmiyati; Muhammad Aufa (Journal of Culture Accounting and Auditing, 2022)
This study aims to determine the magnitude of the influence of learning behavior, emotional intelligence and online learning systems on accounting understanding. The method used in this research is quantitative with primary data in the form of distributing questionnaires to respondents. The sampling technique used purposive sampling technique, obtained a total sample of 106 students. The data analysis technique used in this research is multiple linear regression analysis technique. The results of this study indicate that learning behavior and emotional intelligence have no significant effect on accounting understanding, while the learning system has a significant effect on accounting understanding.